Investigating the Relationship Between Social Networks and the Academic Performance of University Students (Case Study: Faryab University Students) - Arsalan, Zahra; Musammem, Yama (Integrated Journal for Research in Arts and Humanities, 2024)
In recent decades, with the increasing expansion of communication technology, the use of social networks has become one of the most important online activities. However, technology has not only had positive effects on human relationships and personal communication, but its negative effects on academic performance are also well-known. This research focuses on evaluating the negative effects of social networks on academic performance, with a focus on students of Faryab University. This research is applied in terms of classification based on the objective, and can be considered a descriptive-correlational research in terms of methodological classification. The total sample size includes all day students, which is 3000, and a sample of 268 individuals has been selected based on Morgan's table. The questionnaire is used as a data collection tool, and the SPSS software is used for descriptive and inferential statistics (relationship and correlation) for data analysis. The findings of the research indicate a pervasive negative relationship between the use of social networks and academic performance among Faryab University students. While positive interactions such as parental support and strategic personal and peer interactions can increase academic results, potential drawbacks such as distraction, stress, and addiction require a comprehensive approach to deal with the challenges arising from social media.